The effect of top-layer chemistry on the formation of supported lipid bilayers on polyelectrolyte multilayers: primary versus quaternary amines. Issue 47 (21st November 2016) - Diamanti, E.; Andreozzi, P.; Anguiano, R.; Yate, L.; Gregurec, D.; Politakos, N.; Ziolo, R. F.; Donath, E.; Moya, S. E.
Abstract : The influence of the surface chemistry of PEMs on the formation of lipid bilayers is studied here for PEMs with different cationic amines as a top layer, and polystyrene sulfonate (PSS) as a polyanion. Abstract : The influence of the surface chemistry of polyelectrolyte multilayers (PEMs) on the formation of lipid bilayers is studied here for PEMs with either polyallylamine hydrochloride (PAH) or polydiallyldimethylammonium chloride (PDADMAC) as a polycation as a top layer, and polystyrene sulfonate (PSS) as a polyanion. Small unilamellar vesicles (SUVs) composed of phosphatidyl choline and phosphatidyl serine at a 50 : 50 molar ratio are deposited on top of the PEM films. The assembly of the SUVs into bilayers is studied via a quartz crystal microbalance with dissipation (QCM-D) and fluorescence recovery after photobleaching (FRAP). SUV deposition on PDADMAC/PSS results in vesicle adsorption while on PAH/PSS under the same conditions a bilayer is formed mainly due to weak interactions between the quaternary amines of PDADMAC. FRAP measurements confirm that SUVs are not fused on top of PDADMAC/PSS. The effect of phosphate ions, in solution, on the formation of lipid bilayers is also analysed. X-ray photoelectron spectroscopy shows the complexation of phosphate salts to the primary amines of PAH and no interaction with the quaternary amines of PDADMAC. ζ -potential measurements show a potential close to 0 for the PAH/PSS multilayers in PBS while PDADMAC/PSS displays a potential of 25 mV. A model is presented for the formation of lipid bilayers on PAH/PSS PEMs taking into account the role of phosphate ions in decreasing the electrostatic interactions between SUVs and PEMs and the formation of hydrogen bonds between the phospholipids and the primary amines of PAH.